PERAN DINAS PERHUBUNGAN, KOMUNIKASI DAN INFORMATIKA KOTA PEKANBARU DALAM PENGELOLAAN RETRIBUSI PARKIR TAHUN 2013 - Ramadani, Fitri; ", Muchid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Of parking lot as the original one of the components area (PAD) that make a contribution to PAD. Parking fee retribution is done by the Government through the body by many elements that have been determined based on Local regulation No. 3 Year 2009 about of service in the field land transportation Office of Transportation, is Communication and Informatics Pekanbaru . Management of parking lot is not yet been viewed as a matter that is very important in order to support development in area because many potential areas that comes from retribution parking area that is not well-managed because of the lack of initiative and the role Office of Transportation, Communication and Information Pekanbaru to make efforts in to improve regional's original Pekanbaru. The aim of the research is to know the role of Communication Department, and Communication Medical Informatics City of Pekanbaru in management of parking area in 2013 and to know these obstacles by the Transportation, Communication and Informatics City of Pekanbaru in management of parking area in 2013.The method data analysis that is used in this research is descriptive qualitative analysis method that is trying to present based on the phenomena that are and to all the facts related to problems that discussed based on the results of research that is the role of Communication Department and Informatics, Communication Pekanbaru in the management of parking area in 2013.The Department of Relations role, Communications and Information on the field are still many shortcomings in controlling the area path circulation parking, vehicles and retribution that has affected and cheating in wild parking by a spokesman parking this was to make the minimum entry in the sector of parking area in the City Pekanbaru in 2013. Obstacles in the Department of Relations carrying out their role and function to manage of parking at induced the bride price of the officers parking, still over the natural resources construction of a lack of man (the parking lot) that he did not show productivity in performance management in the field, the wild parking in the City Pekanbaru causes entering the Original Regional City of Pekanbaru.Key words : role, Management of Parking, Pekanbaru